EFEKTIFITAS IZIN ATASAN DALAM PERCERAIAN APARATUR SIPIL NEGARA DI WILAYAH HUKUM PENGADILAN AGAMA LIMBOTO - nurhayati hasan (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2018)
Divorce of State Civil Apparatus (ASN) was regulated in accordance with the provisions of PP. 45 in 1990 who must obtain permission from superiors. This research discussed about the effectiveness of superior’s permission to Divorce of Civil State Apparatus (ASN) and consideration factor by superiors in granting divorce permit for state Civil Apparatus (ASN) in Limboto Religious courts area.these research used descriptive qualitative method.types of data are sourced primary and secondary data by technique of collecting through depth interview as well as analysis of document case divorce.checking the validity of data is done through triangulation process.processing and data analysis done through data presentation,verivication,and conclusion. The result showed that ASN superiors who applied for divorce were effective in minimizing ASN divorce in limboto religious courts area.the effectiveness of the regulation of ASN suvervisor’s permission is shown by five indicators of legal effectiveness (read:regulation of the superior’s permission) ASN,namely:(1) understanding of the divorce regulation of ASN divorce(2)socialization of ASN divorce supervisor’s license (3)enforcement of regulation(4)level ofcommunity participation of ASN (5)creation of community life in the limboto religious courts area. There are th of three indicators that indicators that get positive responses namely; (1) understanding of the superior’s license,(2) socialization of the regulation of superior’s,(3) the importance of the ASN divorce superior’s liense to the creation of community lifestyle.the other aspects are: (1) law enforcement and (2) publick participation in realizing the licence of the superior divorce of ASN in the jurisdiction of limboto religious court area is stiil low. The ASN superior’s consideration factor in giving ASN divorce permit is because the parties have no desire improve the household relationship,change of faith,are not enough reason for divorce and to protect the child’s life from negative effect because of bad communication relationship of parents. As recommendation of this policy recommendation, this research is hoped that the religious courts and officials authorized give and refuse permission in order to combined the government regulation concerning marriage and divorce for civil servants can be maximized its enforcement.similarly to the officers of personnel development in the Gorontalo regency and north Gorontalo regency to optimize legal certainty and continuous monitoring infractions committed by ASN.